Biochemical markers of joint tissue damage increase shortly after a joint bleed; an explorative human and canine in vivo study. Issue 1 (January 2015) - van Vulpen, L.F.D.; van Meegeren, M.E.R.; Roosendaal, G.; Jansen, N.W.D.; van Laar, J.M.; Schutgens, R.E.G.; Mastbergen, S.C.; Lafeber, F.P.J.G.
Summary: Objective: Evaluation whether biomarkers of joint damage are sensitive to change shortly after a joint bleed in hemophilia patients and in a canine model of blood-induced joint damage. Methods: Blood and urine samples were collected from 10 hemophilia patients after they reported a joint bleed: within 2 days, after 3–5 days, and 12–14 days. Additionally, 90 days after the bleed a blood and urine sample was taken and considered to represent baseline condition. Commercial serum and urine biomarker assays were performed: urinary C-terminal telopeptide of type II collagen (uCTX-II), serum cartilage oligomeric matrix protein (sCOMP), serum cartilage cleavage product C1, 2C, and serum chondroitin sulfate 846 (sCS846). The same panel of biomarkers was explored in dogs ( n  = 7) after induction of a first joint bleed by intra-articular blood injections. Biosamples were collected at baseline, day 2, 1 and 2 weeks later. Results: In hemophilia patients, levels of uCTX-II and sCS846 increased 5 days after joint bleeding when compared with baseline (+52%; P  = 0.021 and +14%; P  = 0.011, respectively). In dogs, uCTX-II increased statistically significant from day 2 to day 7 (from 75% to 155% of baseline; P  = 0.018), and sCOMP from baseline to day 2 (+46%; P  = 0.028). Conclusions: This study demonstrates that biochemical markers of joint tissue damage increase shortly after a single joint bleed, both in humans with established hemophilic arthropathy (HA) and in an animal model of joint damage upon a first joint bleed. Biomarkers might be useful in monitoring the impact of a joint bleed and in evaluation of treatment of such bleeds.